Determine Personal Status Of Legal Entity: Limited Liability Company (Llc) For Foreign Investment In Indonesia - Silviana, Ria; Andriyan, Andriyan Saputra; Kasmawati, Kasmawati (Universitas Malayati, 2024)
Foreign investment in Indonesia has been on the rise in recent years, with many investors seeking to establish a Limited Liability Company (LLC) as their preferred legal entity. This research aims to examine aspects of determining the personal status of a legal entity, which is an LLC for foreign investment. The personal status of an LLC in Indonesia refers to the legal recognition given to the company as a separate entity from its shareholders or owners. The study explores the complex legal framework and regulations governing foreign investment in Indonesia, with a focus on the unique characteristics and considerations associated with LLCs. Through a comprehensive analysis of relevant laws, policies, and practical implications, this research aims to provide insights into the challenges and opportunities faced by foreign investors seeking to establish LLCs in Indonesia. The research findings are expected to contribute to a better understanding of the personal status of LLCs in the Indonesian legal system and facilitate informed decision-making for foreign entities navigating the complexities of the investment environment in the country.Keywords: Personal Status, Limited Liability Company (LLC), Foreign Investment